2010
DOI: 10.1371/journal.pone.0012361
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Molecular Effects of Diet through Systems Biology: Influence of Herring Diet on Sterol Metabolism and Protein Turnover in Mice

Abstract: BackgroundChanges in lifestyle have resulted in an epidemic development of obesity-related diseases that challenge the healthcare systems worldwide. To develop strategies to tackle this problem the focus is on diet to prevent the development of obesity-associated diseases such as cardiovascular disease (CVD). This will require methods for linking nutrient intake with specific metabolic processes in different tissues.Methodology/Principal FindingLow-density lipoprotein receptor-deficient (Ldlr −/−) mice were fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 44 publications
(57 reference statements)
0
20
0
Order By: Relevance
“…This integrated approach has been recently used to identify the molecular effects of diet on metabolism in mice [27]. An intriguing finding that emerged from our integrated analysis was the co-expression of genes involved in proteasome activation and MHC class I peptide loading in the vagina of mice given CpG ODN or α-GalCer.…”
Section: Discussionmentioning
confidence: 99%
“…This integrated approach has been recently used to identify the molecular effects of diet on metabolism in mice [27]. An intriguing finding that emerged from our integrated analysis was the co-expression of genes involved in proteasome activation and MHC class I peptide loading in the vagina of mice given CpG ODN or α-GalCer.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, our results suggest that Upc2p functions by controlling the enzyme levels at the transcriptional level and that this results in altered fluxes toward ergosterol. This points to Upc2p playing a similar function as the SREBP-1 transcription factor in mammals (Nielsen 2009; Nookaew et al 2010). Our analysis also identified a significant link between ergosterol and 1-acyl-sn-glycerol-3-phosphate acyltransferase ( SLC1 ), which is responsible for the synthesis of phosphatidic acid (PA).…”
Section: Resultsmentioning
confidence: 91%
“…This proposed synergy effect between taurine and long-chain n-3 PUFA, present in herring but not in beef muscle, could be an explanation to the finding of maintained HDL-cholesterol and lower VLDL-cholesterol concentrations in the herring-fed mice. In the transcriptome study performed on a subset of the mice (n=3 per diet group) we found that hepatic Cyp7a1 transcript levels were higher in the herring-fed compared with the beef-fed mice (24). That Cyp7a1 is a promising candidate as a mediator for the herring-induced effects is supported by the finding that Ldlr -/-mice overexpressing Cyp7a1 were resistant to diet-induced hypercholesterolemia (40).…”
Section: Discussionmentioning
confidence: 88%
“…The present study shows the physiological effects of dietary herring vs. beef on body composition, adipocyte size, lipid profiles and atherosclerosis. Transcriptome data derived from a subset of these animals (n=3 per diet group) has previously been published (24).…”
Section: Introductionmentioning
confidence: 99%